Evaluation Of Glucose-6-Phosphate Dehydrogenase Stability In Stored Blood Samples - Jalil, N; Azma, RZ; Mohamed, E; Ithnin, A; Alauddin, H; Baya, SN; Othman, A (Excli Journal Managing Office, 2024)
Indexed by WOS/ Scopus